The effect of first‐time 4‐wheeled walker use on the gait of younger and older adults. Issue 11 (8th October 2021) - Omana, Humberto A.; Madou, Edward; Divine, Alison; Wittich, Walter; Hill, Keith D.; Johnson, Andrew M.; Holmes, Jeffrey D.; Hunter, Susan W.
Abstract: Introduction: The 4‐wheeled walker is intended to enhance balance and gait for older adults. Yet, some research suggests that walking aids increase falls risk. An understanding of the influence of age with walker use on gait performance is required. Objective: To examine the effect of initial 4‐wheeled walker use on spatiotemporal gait parameters between younger and older adults. Design: Cross‐sectional, repeated‐measures. Setting: Community‐dwelling. Participants: Twenty‐five younger (age: 26.5 ± 4.1 years) and 24 older (age: 68.5 ± 10.5 years) adults participated. Younger adults were aged 18 to 35 years, whereas older adults were 50 years or older. Included were people not requiring the use of a walking aid, and those able to converse in English. Interventions: Not applicable. Main Outcome Measure(s): Gait velocity and stride time variability were recorded using accelerometers. Gait was examined under three conditions: unassisted walking; walking with a 4‐wheeled walker; and walking with a 4‐wheeled walker while completing a secondary task. Conditions were performed across two walking paths: straight and figure‐of‐8 Walk Test. Separate mixed‐methods analyses of variance (ANOVAs; within‐subject: condition/path; between‐subject: group) were used for statistical analyses. Results: Velocity was lower when walking using a walker while completing a cognitive task ( p  < .001), in the figure‐of‐8 Walk Test ( p  < .001), and in older adults ( p  = .001). Stride time variability increased with walking path and condition difficulty ( p  < .001) for the straight path versus the figure‐of‐8 Walk Test. Conclusions: Using a 4‐wheeled walker resulted in a slower and more inconsistent gait pattern across both age groups. Walking more complex configurations resulted in the prioritization of gait over the cognitive task while performing the dual‐task conditions. No evidence of an age‐related difference in the effect of initial walker use on gait was observed. Nonetheless, walkers are cognitively demanding and their introduction should warrant a clinical follow‐up.